Resolvin E1 (RvE1) attenuates LPS induced inflammation and subsequent atrophy in C2C12 myotubes. Issue 7 (25th March 2018) - Baker, Luke A.; Martin, Neil R. W.; Kimber, Marc C.; Pritchard, Gareth J.; Lindley, Martin R.; Lewis, Mark P.
Abstract: Resolution of inflammation is now known to be an active process which in part is instigated and controlled by specialized pro‐resolving lipid mediators (SPM's) derived from dietary omega‐3 fatty acids. Resolvin E1 (Rv E1 ) is one of these SPM's derived from the omega‐3 fatty acid eicosapentaenoic acid. Using both molecular and phenotypic functional measures we report that in a model of Lipopolysaccharide (LPS) induced inflammation, Rv E1 attenuated mRNA levels of both interlukin‐6 and monocyte chemoattractant protein‐1 whilst having no effect on tumor necrosis factor‐α or interlukin‐1β in C2C12 skeletal muscle myotubes. Findings at the molecular level were transferred into similar changes in extracellular protein levels of the corresponding genes with the greatest attenuation being noted in IL‐6 protein concentrations. Rv E1 instigated beneficial morphological changes through the prevention of LPS induced skeletal muscle atrophy, in tandem with attenuation of the LPS induced reduction in contractile force in tissue engineered skeletal muscle. These findings demonstrate, in our model of endotoxin induced inflammation in skeletal muscle, that Rv E1 has pro‐resolving properties in this cell type. Our data provides rationale for further investigation into the mechanistic action of Rv E1 in skeletal muscle, with the vision of having potential benefits for the prevention/resolution of in‐vivo skeletal muscle atrophy. Abstract : The specialized pro‐resolving mediator Resolvin E1 attenuates endotoxin induced inflammatory signaling and downstream atrophy in skeletal muscle myotubes. Potential for nutritional therapeutic intervention in cachexic disease states.